1970
DOI: 10.1126/science.170.3959.749
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Reaction of Mammalian Spermatozoa on Gelatin Membranes

Abstract: The acrosomes of spermatozoa of several mammalian species show proteolytic activity when applied to fixed gelatin membranes. The technique permits continuous observation of the enzymatic reaction of an individual spermatozoon. Release of the enzyme occurs solely in the region of the acrosome, in a manner which is species-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

1972
1972
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 5 publications
0
21
0
2
Order By: Relevance
“…This would afford a passage for the organism through the mucus layer to the susceptible cell, to which the K88 antigen would then allow it to adhere. While this mechanism is hypothetical, it is based on a similar enzymic arrangement which allows spermatozoa to penetrate the mucus of the mammalian cervix (Gaddum & Blandau, 1970;Blandau, 1973). Once adherence is established the bacterium is in a more favourable environment than that of the lumen of the gut; it can now proliferate and cause (if it also produces enterotoxins) disease.…”
Section: Discussionmentioning
confidence: 99%
“…This would afford a passage for the organism through the mucus layer to the susceptible cell, to which the K88 antigen would then allow it to adhere. While this mechanism is hypothetical, it is based on a similar enzymic arrangement which allows spermatozoa to penetrate the mucus of the mammalian cervix (Gaddum & Blandau, 1970;Blandau, 1973). Once adherence is established the bacterium is in a more favourable environment than that of the lumen of the gut; it can now proliferate and cause (if it also produces enterotoxins) disease.…”
Section: Discussionmentioning
confidence: 99%
“…It seems to be generally agreed, however that acrosin (or sperm trypsin-like enzyme) is responsible for sperm penetration of the zona pellucida (Srivastava et al, 1965;Stambaugh et al, 1969;Zaneveld et al, 1973;, but the evidence that these particular enzymes are even found in the acrosome has been largely circumstantial. It has been based on changes in sperm morphology after enzyme extraction (Pedersen, 1972;Brown & Hartree, 1974;Churg et al, 1974;Srivastava et al, 1974), on the localization of labelled non-specific enzyme inhibitors (Stambaugh & Buckley, 1972) and on the detection of proteolytic activity using gelatin films (Gaddum & Blandau, 1970;Benitez-Bribiesca & Velazquez-Meza, 1972;Gaddum-Rosse & Blandau, 1972;Penn et al, 1972;Allen et al, 1974). This proteolytic activity is unlikely to be specific as there is increasing evidence that more than one proteinase exists in spermatozoa (Dott & Dingle, 1968;Allison & Hartree, 1970;Multimaki & Niemi, 1972;Yanagimachi & Teichman, 1972;Bernstein & Teichman, 1973;Srivastava & Foley, 1973).…”
mentioning
confidence: 96%
“…It is concluded that (pro)acrosin (acrosin-inhibitor) (Gaddum and Blandau, 1970 ;Sakai and Yasuda, 1981 ;Green and Hockaday, 1978 ;Harrison et al, 1982 ;Huneau et al, 1983) Proacrosin content and radioactivity were assayed in the fractions, and those having proacrosin activity were pooled. The pooled fractions of ( 14 C)-glucosamine-labelled material were further purified by hydrophobic chromatography on a Spheron P-300 1 x 4.8 cm column equilibrated with 0.3 M acetic acid, 0.05 M NaCl, pH 3.0 (Zelezna and 6echov6, 1982).…”
mentioning
confidence: 99%